2022
DOI: 10.1039/d2sd00082b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and direct quantification of the SARS-CoV-2 virus with an ultrasensitive nanobody-based photonic nanosensor

Abstract: The coronavirus (CoV) disease 2019 (COVID-19) is expected to become endemic in the upcoming years, meaning that the worldwide society shall be prepared to routinely manage the highly contagious respiratory...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…The SARS-CoV-2 viruses were produced and provided by the National Institute of Infectious Diseases (INMI) of Rome (Italy), and they were duly inactivated through ultraviolet (UV) irradiation (15 min, λ 254 nm), which was verified by inoculating the viruses on VeroE6 cells and confirming no viral replication for three consecutive passages. The UV inactivation treatment is intended to only affect the genomic material of the virus (RNA), therefore unaltering the external structure of the viral particles allowing their safely use in BSL2 laboratories ( Ruiz-Vega et al, 2022 ). SARS-CoV-2 samples at different titers (10 3 to 5 × 10 5 TCID50/mL) were prepared by serial dilution in standard buffer (HEPES 50 mM pH 7.4) and flowed over the biomimetic scaffold on the sensor surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SARS-CoV-2 viruses were produced and provided by the National Institute of Infectious Diseases (INMI) of Rome (Italy), and they were duly inactivated through ultraviolet (UV) irradiation (15 min, λ 254 nm), which was verified by inoculating the viruses on VeroE6 cells and confirming no viral replication for three consecutive passages. The UV inactivation treatment is intended to only affect the genomic material of the virus (RNA), therefore unaltering the external structure of the viral particles allowing their safely use in BSL2 laboratories ( Ruiz-Vega et al, 2022 ). SARS-CoV-2 samples at different titers (10 3 to 5 × 10 5 TCID50/mL) were prepared by serial dilution in standard buffer (HEPES 50 mM pH 7.4) and flowed over the biomimetic scaffold on the sensor surface.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only a recent study has reported a plasmonic sensor for the quantification of whole SARS-CoV-2 virus particles, achieving a detection limit of 370 viral particles per mL (vp/mL) ( Huang et al, 2021 ), which is within the same range of our approach but using pseudotyped viruses, a secondary amplification step with gold nanoparticles, and not validated with real samples. On the other hand, our group developed a nanophotonic interferometric sensor for COVID-19 diagnostics demonstrating direct SARS-CoV-2 virus detection with detection limits below 100 TCID50/mL ( Ruiz-Vega et al, 2022 ). Herein, we have achieved similar results employing a conventional and user-friendly SPR technology with an innovative sensor biofunctionalization, which is considered to enhance the SARS-CoV-2 virus binding interaction by mimicking the human cell micro-environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another label-free, interferometric integrated optical biosensor construction is the bimodal waveguide interferometer, which technology has emerged in recent years. These devices have a small footprint and their performance has been demonstrated in the case of several target detection from fluid samples, e.g., microRNA marker [ 61 ], SARS-CoV-2 viral proteins [ 62 ], and bacteria [ 63 , 64 ]. The above-mentioned studies clearly show the impact of the application of such integrated optical interferometric biosensors in chip devices as incorporated sensors.…”
Section: Optical Biosensors As Promising Candidates For Incorporated ...mentioning
confidence: 99%